QUALIMETRIC MODEL OF RUSSIAN INTERIOR MINISTRY`S HIGHER EDUCATION SYSTEM - Elena Nikolaevna Grivennaja (Вестник Северо-Кавказского федерального университета, 2022)
This article presents a model for monitoring the quality of education in the Russian Ministry of Internal Affairs from the position of educational qualimetry, clarifies the conceptual apparatus of the problem, de- scribes the object and the subject of monitoring the quality of education, its strategy, goals, objectives, func- tions, methods, principles and implementation phases.